27a⁰c³ for a =⅔, c = -⅓



need answer and if you could explain how to solve problem that would be much appreciated.​

Respuesta :

Answer:

- 1

Step-by-step explanation:

Using the rules of exponents

[tex]a^{0}[/tex] = 1

[tex](a^n)^{m}[/tex] = [tex]a^{nm}[/tex]

Given

27[tex]a^{0}[/tex][tex](-\frac{1}{3}) ^{3}[/tex]

Note [tex]a^{0}[/tex] = 1 for any value of a, thus

= 27 × 1 × - [tex]\frac{1}{3^{3} }[/tex]

= 27 × 1 × - [tex]\frac{1}{27}[/tex] ← cancel the 27 on numerator/ denominator

= 1 × - 1

= - 1

ACCESS MORE